Carbon-based catalyst loaded with metal palladium and sulfur as well as preparation method and application of carbon-based catalyst
By supporting metal palladium and sulfur carbon-based catalysts, the problem of insufficient catalytic activity of active sites in electrochemical synthesis of hydrogen peroxide is solved, and high selective production of hydrogen peroxide is achieved, and excellent redox performance is achieved.
Patent Information
- Application Number
- CN202311134267.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
In the existing methods for electrochemical synthesis of hydrogen peroxide, the catalytic activity of the active site is too weak or too strong, making it difficult to effectively form the intermediate OOH, resulting in a low selectivity of hydrogen peroxide.
Using a carbon-based catalyst supported by metal palladium and sulfur, a catalyst supported by palladium and small clusters was prepared by mixing the porous carbon material with a precursor of sulfur and palladium, heat treatment and ultraviolet irradiation.
This catalyst has excellent redox properties, high selectivity for hydrogen peroxide, and can produce hydrogen peroxide efficiently in acidic media.
Smart Images

Figure CN119553304A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a carbon-based catalyst loaded with metal palladium and sulfur, and a preparation method and application thereof. Background Art
[0002] With economic development and sustained population growth, the world energy crisis is becoming increasingly serious. The development of new energy and the full utilization of energy are the key to solving the energy problem. The production of chemicals is one of the important sources of energy consumption. Hydrogen peroxide is one of the 100 most important chemicals in the world. Therefore, the high-efficiency and sustainable production of hydrogen peroxide is one of the issues that need to be studied urgently. Among the various synthesis methods of hydrogen peroxide, electrochemical synthesis has the advantages of high energy efficiency, low production risk, and high product purity. It can be produced continuously, on a small scale, and in a decentralized manner, and has a wide range of uses.
[0003] The electrochemical synthesis of hydrogen peroxide mainly utilizes the cathode oxygen reduction method. There are two processes in the electrochemical cathode oxygen reduction: the two-electron process and the four-electron process. For the oxygen reduction reaction (ORR), oxygen molecules are first adsorbed onto the active site, and then the intermediate OOH is formed. In the next step, the active site reacts selectively according to the strength of the binding ability of the oxygen molecule. If the OO bond is broken, the four-electron process is carried out, and the formed OH combines with H to generate water. If it is not broken, the intermediate OOH combines with one H to generate hydrogen peroxide. For the electrosynthesis of hydrogen peroxide, if the catalytic activity of the active site is too weak, it is difficult to form the intermediate OOH; if the catalytic activity is too strong, the OO bond is broken. Therefore, in order to inhibit the formation of water as a side reaction product, it is of great significance to prepare electrocatalytic oxygen reduction materials with appropriate binding ability with oxygen molecules for the efficient electrosynthesis of hydrogen peroxide. Summary of the invention
[0004] The purpose of the present invention is to provide a carbon-based catalyst loaded with metal palladium and sulfur, and a preparation method and application thereof. The catalyst of the present invention has excellent catalytic activity for preparing hydrogen peroxide by electrocatalytic oxygen reduction reaction and has high selectivity for hydrogen peroxide.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a carbon-based catalyst loaded with metallic palladium and sulfur, wherein the catalyst contains a porous carbon material, sulfur and palladium, and based on the total weight of the catalyst, the sulfur content is 0.2-5.0 weight%, and the palladium content is 0.2-5.0 weight%; the palladium is loaded on the porous carbon material in the form of single atomic palladium and / or clustered palladium.
[0006] Optionally, based on the total weight of the catalyst, the sulfur content is 0.2-5.0 wt %, and the palladium content is 0.2-5.0 wt %.
[0007] Optionally, the mesopore volume of the catalyst accounts for 75.0-99.0% of the total pore volume, and the micropore volume accounts for 1.0-25.0% of the total pore volume.
[0008] The second aspect of the present invention provides a method for preparing the catalyst provided by the first aspect of the present invention, the method comprising:
[0009] S1, mixing a porous carbon material and a sulfur precursor, and heat-treating the obtained mixture in an inert atmosphere to obtain a sulfur-modified carbon material;
[0010] S2. Mixing the sulfur-modified carbon material, the palladium precursor and water, irradiating the obtained mixture with ultraviolet light, and taking out a solid product.
[0011] Optionally, in step S2, the weight ratio of the sulfur-modified carbon material to the palladium precursor is 100:(0.2-5); the power of the ultraviolet lamp used for the ultraviolet irradiation is 200-2000W, the illumination time is 1-5h, and the atmosphere is an inert atmosphere.
[0012] Optionally, in step S1, the molar ratio of the porous carbon material to the sulfur precursor is 3:1-1:3; the heat treatment conditions include: a temperature of 500-1200° C. and a time of 1-5 hours.
[0013] Optionally, the porous carbon material is selected from one or more of Vulcan-X72, BP2000, Ketjen black, acetylene black and graphitized carbon black;
[0014] The sulfur precursor is selected from one or more of thiourea, thioacetamide, dipropyl disulfide, diphenyl disulfide and diallyl disulfide;
[0015] The palladium precursor is one or more of palladium nitrate, palladium chloride, palladium sulfate and dinitrosodiammine palladium.
[0016] Optionally, the method further comprises: acid-washing the porous carbon material to remove impurities and water-washing the porous carbon material and then mixing it with the sulfur precursor; the acid used for the acid-washing is one or more of nitric acid, sulfuric acid and hydrochloric acid, and the concentration of the acid is 0.5-5.0 mol / L.
[0017] Optionally, in step S2, the mixing of the sulfur-modified carbon material, the palladium precursor and water comprises: mixing the sulfur-modified carbon material and water and then performing ultrasonic dispersion, and mixing the dispersed mixture with the palladium precursor.
[0018] The third aspect of the present invention provides a use of the catalyst provided by the first aspect of the present invention in an electrocatalytic oxygen reduction reaction in an acidic medium.
[0019] Through the above technical scheme, the metal palladium in the catalyst of the present invention is loaded on the porous carbon material in the form of single atom or small cluster of palladium, and the catalyst has rich interface structure, rich micropores and mesoporous structure, which is conducive to the full contact between the electrolyte and the active site and the mass transfer process. The catalyst has good redox performance and high selectivity for hydrogen peroxide.
[0020] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0022] Figure 1 This is a TEM image of the catalyst obtained in Example 1.
[0023] Figure 2 is the XRD pattern of the catalyst obtained in Example 1.
[0024] Figure 3 This is the XPS spectrum of the catalyst obtained in Example 1.
[0025] Figure 4 This is the XPS spectrum of the catalyst obtained in Example 1.
[0026] Figure 5 It is the linear voltammetric curve of the catalyst obtained in Example 1 in 0.1M HClO4 solution.
[0027] Figure 6 This is the hydrogen peroxide selectivity curve of the catalyst obtained in Example 1 in 0.1M HClO4 solution.
[0028] Figure 7 This is a SEM image of the catalyst obtained in Example 2.
[0029] Figure 8 is the XRD pattern of the catalyst obtained in Example 3.
[0030] Fig. 9 This is a TEM image of the catalyst obtained in Example 4.
[0031] Fig.10 This is the curve of hydrogen peroxide changing over time when the catalyst obtained in Example 4 is applied to cathode electrosynthesis of hydrogen peroxide. DETAILED DESCRIPTION
[0032] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0033] The first aspect of the present invention provides a carbon-based catalyst loaded with metallic palladium and sulfur, wherein the catalyst contains a porous carbon material, sulfur and palladium, wherein the sulfur content is 0.2-5.0 wt%, and the palladium content is 0.2-5.0 wt%, based on the total weight of the catalyst; and the palladium is loaded on the porous carbon material in the form of single atomic palladium and / or clustered palladium.
[0034] The single-atom palladium and / or cluster palladium in the catalyst of the present invention are all palladium smaller than the nanometer scale. The existence form of palladium in the catalyst of the present invention can be proved by the combined characterization of XRD and TEM. The catalyst composition of the present invention is analyzed by XRD, and it can be known that there is no crystalline metal palladium in the catalyst, and there are no obvious palladium nanoparticles in the TEM photo. The above can prove that palladium exists in the catalyst in the form of single-atom palladium and / or cluster palladium. Characterization of the catalyst by XPS can prove the presence of palladium in the catalyst of the present invention. In the catalyst of the present invention, palladium is embedded in the form of single atoms or small clusters of palladium atoms on the surface rich in porous carbon materials, so that it has a rich interface structure, and the catalytic material has rich micropores and mesoporous structures, which is conducive to the full contact between the electrolyte and the active sites, and is conducive to the mass transfer process. Therefore, the catalyst of the present invention has excellent oxygen reduction catalytic performance, and has a high selectivity for hydrogen peroxide.
[0035] In a specific embodiment of the present invention, based on the total weight of the catalyst, the sulfur content is 0.4-4.0% by weight, and the palladium content is 0.3-3.0% by weight. The catalyst having the above composition has better catalytic reaction activity and selectivity for hydrogen peroxide.
[0036] In a specific embodiment of the present invention, the mesopore volume of the catalyst accounts for 75.0-99.0% of the total pore volume, and the micropore volume accounts for 1.0-25.0% of the total pore volume. The mesopore volume, micropore volume and total pore volume of the catalyst are measured by BET nitrogen adsorption method. The catalyst of the present invention has abundant micropores and mesoporous structures, which is conducive to the full contact between the electrolyte and the active sites, so that it has a higher catalytic activity.
[0037] The second aspect of the present invention provides a method for preparing the catalyst provided in the first aspect of the present invention, the method comprising: S1, mixing a porous carbon material and a sulfur precursor, and heat-treating the obtained mixture in an inert atmosphere to obtain a sulfur-modified carbon material; S2, mixing the sulfur-modified carbon material, a palladium precursor and water, irradiating the obtained mixture with ultraviolet light, and taking out a solid product.
[0038] The method of the present invention adopts an ultraviolet light reduction method to prepare a catalyst in one step. In the obtained catalyst, palladium exists in the form of single atoms or smaller clusters on a sulfur-modified carbon material. The entire material is rich in micropores and mesopores, exhibits excellent oxygen reduction catalytic activity in an acidic medium, and can produce hydrogen peroxide with high selectivity. It has broad prospects and can be widely used in applications involving electrocatalytic oxygen reduction reactions.
[0039] According to the present invention, in step S2, the weight ratio of the sulfur-modified carbon material to the palladium precursor can vary within a wide range. In a specific embodiment of the present invention, the weight ratio of the sulfur-modified carbon material to the palladium precursor is 100:(0.2-5), preferably 100:(0.3-3); the power of the ultraviolet lamp used for the ultraviolet irradiation is 200-2000W, and the illumination time is 1-5h; preferably, the power is 300-1500W, and the illumination time is 2-4h.
[0040] In a specific embodiment of the present invention, in step S1, the molar ratio of the porous carbon material to the sulfur precursor is 3:1-1:3, preferably 5:2-2:5; the heat treatment conditions include: temperature of 500-1200°C, time of 1-5 hours, and an inert atmosphere; preferably, temperature of 600-1000°C, time of 2-4 hours, and an inert atmosphere. In the present invention, the inert atmosphere contains an inert gas, such as nitrogen, argon, helium, etc. Under the above conditions, a catalyst with better oxygen reduction catalytic performance and selectivity can be prepared.
[0041] According to the present invention, the porous carbon material may be well known to those skilled in the art. In a specific embodiment of the present invention, the porous carbon material is selected from one or more of Vulcan-X72, BP2000, Ketjen black, acetylene black and graphitized carbon black; the sulfur precursor is selected from, preferably one or more of thiourea, thioacetamide, dipropyl disulfide, diphenyl disulfide and diallyl disulfide; the palladium precursor may be an organic palladium salt and / or an inorganic palladium salt, preferably one or more of palladium nitrate, palladium chloride, palladium sulfate and dinitrodiammine palladium.
[0042] In a specific embodiment of the present invention, the method further comprises: acid-washing the porous carbon material to remove impurities and water-washing and then mixing it with the sulfur precursor; the acid used for the acid washing is one or more of nitric acid, sulfuric acid and hydrochloric acid, and the concentration of the acid is 0.5-5.0 mol / L.
[0043] In a specific embodiment of the present invention, in step S2, the mixing of the sulfur-modified carbon material, the palladium precursor and water comprises: mixing the sulfur-modified carbon material and water and then performing ultrasonic dispersion, and mixing the dispersed mixture with the palladium precursor.
[0044] A third aspect of the present invention provides use of the catalyst provided in the first aspect in an electrocatalytic oxygen reduction reaction in an acidic medium.
[0045] The catalyst of the invention has high catalytic activity in the electrocatalytic oxygen reduction reaction in an acidic medium and high selectivity for hydrogen peroxide.
[0046] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0047] The chemical reagents used in the following examples and comparative examples are commercially available.
[0048] Example 1
[0049] S1, acetylene black with 1mol L -1 The mixture was washed with sulfuric acid to remove impurities, and then washed with water for later use; 1.5 g of acetylene black obtained by the treatment was ground and mixed with 0.5 g of dipropyl disulfide, and then subjected to high-temperature heat treatment at 600° C. for 3 h under an argon atmosphere to obtain sulfur-modified acetylene black;
[0050] S2. Place 180 mg of sulfur-modified acetylene black in 200 mL of deionized water and disperse it by ultrasonic for 2 h. Add 1.72 mg of palladium sulfate as a precursor, stir and mix well. Place it under a 1000 W ultraviolet lamp for 2 h to prepare a sulfur-modified acetylene black-loaded metal palladium catalyst.
[0051] TEM image of sulfur-modified acetylene black supported metal palladium catalyst is shown in Figure 1 There are no obvious palladium nanoparticles in the photo; and its XRD analysis spectrum is shown in Figure 2 There is no X-ray characteristic diffraction peak of metal palladium in this spectrum. The above characterization shows that the palladium in the catalyst does not exist in the form of crystals, but in the form of single atomic palladium or small-scale clusters of palladium. At the same time, XPS characterization of the catalyst is carried out as follows Figure 3 and Figure 4 As shown, the characteristic peak of palladium is found in the XPS spectrum, proving that the catalyst contains palladium. The catalyst has excellent oxygen reduction catalytic activity. The linear voltammetric curve of the catalyst in 0.1M HClO4 solution is shown in Figure 5 As shown, the selectivity for hydrogen peroxide is Figure 6 shown.
[0052] Example 2
[0053] S1. Vulcan-X72 was treated with 1 mol L -1 The product was washed with hydrochloric acid to remove impurities, and then washed with water for later use; 1.5 g of Vulcan-X72 obtained by the treatment was ground and mixed with 1.5 g of thioacetamide, and then subjected to high-temperature heat treatment at 800°C in an argon atmosphere for 4 hours to obtain sulfur-modified Vulcan-X72;
[0054] S2. Place 180 mg of sulfur-modified Vulcan-X72 in 200 mL of deionized water and disperse it by ultrasonic for 2 h. Add 6.86 mg of palladium sulfate as a precursor, stir and mix well. Place it under a 500 W ultraviolet lamp for 3 h to prepare a sulfur-modified Vulcan-X72-loaded metal palladium catalyst.
[0055] The SEM image of sulfur-modified Vulcan-X72 supported palladium catalyst is shown in Figure 7 , there are no obvious palladium nanoparticles in this image.
[0056] Example 3
[0057] S1, graphitized carbon black was treated with 1 mol L -1 The mixture was washed with sulfuric acid to remove impurities, and then washed with water for later use; 1.5 g of graphitized carbon black obtained by the above treatment was ground and mixed with 1.0 g of diphenyl disulfide, and then subjected to high-temperature heat treatment at 1000° C. in an argon atmosphere for 1 hour to obtain sulfur-modified graphitized carbon black;
[0058] S2. Place 180 mg of sulfur-modified graphitized carbon black in 200 mL of deionized water and disperse it by ultrasonic for 1 h. Add 9.02 mg of palladium chloride as a precursor, stir and mix well. Place it under a 1000 W ultraviolet lamp for 2 h to prepare a sulfur-modified graphitized carbon black-loaded metal palladium catalyst.
[0059] The XRD spectrum of sulfur-modified graphitized carbon black supported metal palladium catalyst is shown in Figure 8 , there is no X-ray diffraction peak of metal palladium in this figure.
[0060] Example 4
[0061] S1, Ketjen black with 3 mol L -1 The mixture was washed with hydrochloric acid to remove impurities, and then washed with water for later use; 1.5 g of Ketjen black obtained by the above treatment was ground and mixed with 2.5 g of thioacetamide, and subjected to high-temperature heat treatment at 1200° C. in an argon atmosphere for 2 hours to obtain sulfur-modified Ketjen black;
[0062] S2. Place 180 mg of sulfur-modified Ketjen black in 200 mL of deionized water and disperse it by ultrasonic for 2 h, add 3.91 mg of palladium nitrate as a precursor, stir and mix well, and place it under an 800 W ultraviolet lamp for 4 h to prepare a sulfur-modified Ketjen black-loaded metal palladium catalyst.
[0063] TEM image of sulfur-modified Falkin black supported metal palladium catalyst is shown in Fig. 9 The curve of hydrogen peroxide change over time when the catalyst is used for cathode electrosynthesis of hydrogen peroxide is shown in Fig.10 .
[0064] Example 5
[0065] The same method as in Example 1 was used, except that in step S1, 1.5 g of acetylene black and 0.5 g of dipropyl disulfide were ground and mixed uniformly, and then subjected to high-temperature heat treatment at 400° C. for 8 h in an argon atmosphere.
[0066] Example 6
[0067] The same method as in Example 1 is used, except that in step S2, the power of the ultraviolet lamp used for ultraviolet irradiation is 100 W and the irradiation time is 24 h.
[0068] Example 7
[0069] The same method as in Example 1 is used, except that in step S2, the power of the ultraviolet lamp used for ultraviolet irradiation is 150 W and the irradiation time is 20 h.
[0070] Comparative Example 1
[0071] Preparation method of carbon-based material-supported cobalt hydrogen peroxide catalyst:
[0072] Steps: 0.33 mol / L cobalt salt solution is added dropwise to 0.4 mol / L 2-methylimidazole solution, the molar ratio of cobalt salt to 2-methylimidazole is 1:8, and the reaction is stirred at room temperature for 4 hours to generate a purple precipitate, the precipitate is separated and washed with deionized water and anhydrous ethanol several times in turn, and the MOF material ZIF-67 is obtained after vacuum drying at 60°C. Under a protective atmosphere, the ZIF-67 is subjected to a high-temperature annealing at 650°C for 4 hours to obtain a carbonized product. The carbonized product is mixed with phosphorus and placed in a high-temperature tube furnace with selenium. The mass ratio of the carbonized product to red phosphorus and selenium powder is 100:52.3:200, and a high-temperature solid-phase reaction at 600°C is carried out under vacuum conditions for 4 hours. After the reaction is completed, it is cooled, the reaction product is transferred and subjected to a secondary heat treatment at 500°C for 30 minutes under a protective atmosphere, and the electrosynthetic hydrogen peroxide catalyst is obtained after cooling.
[0073] Test Case
[0074] A three-electrode system was used to investigate the redox catalytic performance of the catalyst.
[0075] The working electrode is a rotating disk electrode: the disk electrode is working electrode No. 1; the platinum ring electrode is working electrode No. 2, which collects the generated hydrogen peroxide by applying a potential; the counter electrode is a platinum electrode; the reference electrode is a saturated calomel electrode (SCE), and the electrolyte is 0.1 mol L -1 HClO4 solution. Potential converted to reversible hydrogen electrode (RHE) scale (V RHE =V SCE +0.3V). In a fixed potential scanning range, the disk electrode was subjected to a 10mV s -1 The speed was set to 1600 rpm, the platinum ring potential was fixed at 1.2 V, and the disk current (I D ) and the ring current (I R ) and calculate the hydrogen peroxide yield (H2O2%).
[0076] The calculation formula is:
[0077] Where N is the ring electrode collection efficiency (N = -I R / I D ), and take the average value of 0.255 obtained from the test.
[0078] Table 1
[0079]
[0080] It can be seen from the above that the catalyst of the present invention has excellent oxygen reduction catalytic performance and high selectivity for hydrogen peroxide.
[0081] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0082] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0083] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A carbon-based catalyst loaded with metallic palladium and sulfur, the catalyst comprising a porous carbon material, sulfur and palladium, wherein the sulfur content is 0.2-5.0 wt % and the palladium content is 0.2-5.0 wt % based on the total weight of the catalyst; the palladium is loaded on the porous carbon material in the form of single atomic palladium and / or clustered palladium.
2. The catalyst according to claim 1, wherein Based on the total weight of the catalyst, the sulfur content is 0.4-4.0 weight %, and the palladium content is 0.3-3.0 weight %.
3. The catalyst according to claim 1, wherein The mesopore volume of the catalyst accounts for 75.0-99.0% of the total pore volume, and the micropore volume accounts for 1.0-25.0% of the total pore volume.
4. A method for preparing the catalyst according to any one of claims 1 to 3, the method comprising: S1, mixing a porous carbon material and a sulfur precursor, and heat-treating the obtained mixture in an inert atmosphere to obtain a sulfur-modified carbon material; S2. Mixing the sulfur-modified carbon material, the palladium precursor and water, irradiating the obtained mixture with ultraviolet light, and taking out a solid product.
5. The method according to claim 4, wherein: In step S2, the weight ratio of the sulfur-modified carbon material to the palladium precursor is 100:(0.2-5); the power of the ultraviolet lamp used for the ultraviolet irradiation is 200-2000W, and the irradiation time is 1-5h.
6. The method according to claim 4, wherein: In step S1, the molar ratio of the porous carbon material to the sulfur precursor is 3:1-1:3; the heat treatment conditions include: temperature of 500-1200°C, time of 1-5 hours, and an inert atmosphere.
7. The method according to claim 4, wherein: The porous carbon material is selected from one or more of Vulcan-X72, BP2000, Ketjen black, acetylene black and graphitized carbon black; The sulfur precursor is selected from one or more of thiourea, thioacetamide, dipropyl disulfide, diphenyl disulfide and diallyl disulfide; The palladium precursor is one or more of palladium nitrate, palladium chloride, palladium sulfate and dinitrosodiammine palladium.
8. The method according to claim 4, wherein: The method also includes: acid-washing the porous carbon material to remove impurities and water-washing before mixing it with the sulfur precursor; the acid used in the acid-washing is one or more of nitric acid, sulfuric acid and hydrochloric acid, and the concentration of the acid is 0.5-5.0 mol / L.
9. The method according to claim 4, wherein: In step S2, the mixing of the sulfur-modified carbon material, the palladium precursor and water comprises: mixing the sulfur-modified carbon material and water, performing ultrasonic dispersion, and mixing the dispersed mixture with the palladium precursor.
10. Use of the catalyst according to any one of claims 1 to 3 in an electrocatalytic oxygen reduction reaction in an acidic medium.